2019
DOI: 10.1103/physrevb.100.195127
|View full text |Cite
|
Sign up to set email alerts
|

Surface electronic structure of the wide band gap topological insulator PbBi4Te4Se3

Abstract: By means of angle-resolved photoemission spectroscopy (ARPES) measurements and density functional theory (DFT) calculations, the electronic band structure of the topological insulator PbBi 4 Te 4 Se 3 for both five-layer and seven-layer surface terminations is investigated. The measured and calculated band structure features are in good agreement and indicate two well-resolved topological surface states with distinct spatial localizations within bulk band gap of about 0.3 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…On the other hand, the bulk band gap in PbBi 4 Te 6 Se is 1.5 times larger, proving that the substitution of just one atom (Te) with a lighter one (Se) within the unit cell in the QL has an important impact on the bulk band gap value. This finding is in agreement with recent studies, which have predicted a bulk band gap of 270 meV in PbBi 4 Te 3 Se 3 [35] and of 300 meV in PbBi 4 Te 3 S 3 [36].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…On the other hand, the bulk band gap in PbBi 4 Te 6 Se is 1.5 times larger, proving that the substitution of just one atom (Te) with a lighter one (Se) within the unit cell in the QL has an important impact on the bulk band gap value. This finding is in agreement with recent studies, which have predicted a bulk band gap of 270 meV in PbBi 4 Te 3 Se 3 [35] and of 300 meV in PbBi 4 Te 3 S 3 [36].…”
Section: Resultssupporting
confidence: 94%
“…For both compounds we also observe M-shaped bulk bands with an energy maximum of E B 0.7 eV and wave number k ±0.14 Å −1 . Such M-shaped states are due to intrinsic quantization effects [38], also reported for similar compounds, such as PbBi 4 Te 7 [23], PbBi 6 Te 10 [25], PbBi 4 Te 4 S 3 [39], PbBi 4 Te 4 Se 3 [35], and GeBi 4 Te 7 [40]. The diffuse photoemission intensity measured at the¯ point close to the Fermi level is attributed to partial occupation of the conduction band.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…tetradymite-like A IV B V 2 Te 4 , A IV B V 4 Te 7 , A IV B V 6 Te 10 and other compounds formed in A IV -B V -Te systems (A IV -Ge, Sn, Pb; B V -Sb, Bi) are thermoelectric materials with low thermal conductivity [1][2][3][4]. Recent studies have shown that these compounds also have threedimensional topological insulator properties [5][6][7][8][9] and are perspective for use in spintronics, quantum computing, medicine, and security systems [10][11][12][13][14][15].…”
Section: Ternarymentioning
confidence: 99%
“…They are distinctive from TRS-broken Chern insulators, exhibiting a quantum anomalous Hall effect. , From the fact that the gapless boundary states host a unique helical spin texture and can carry dissipationless spin currents, TIs have been suggested to be useful for various applications, e.g., quantum computation and spintronic devices. , In spite of such remarkable potential, the practical applications at room temperature have been severely limited until now, largely owing to the small band gaps in real materials. For example, Bi 2 Se 3 is arguably the most actively explored, and its band gap is ∼0.3 eV. Therefore, searching for larger band gap Z 2 TIs poses an important challenge and is indeed under active investigation. …”
Section: Introductionmentioning
confidence: 99%